Housing Market Dynamics in Africa - Bah, El-hadj M. (Palgrave Macmillan UK, 2018)
This open access book utilizes new data to thoroughly analyze the main factors currently shaping the African housing market. Some of these factors include the supply and demand for housing finance, land tenure security issues, construction cost conundrum, infrastructure provision, and low-cost housing alternatives. Through detailed analysis, the authors investigate the political economy surrounding the continent's housing market and the constraints that behind-the-scenes policy makers need to address in their attempts to provide affordable housing for the majority in need. With Africa's urban population growing rapidly, this study highlights how broad demographic shifts and rapid urbanization are placing enormous pressure on the limited infrastructure in many cities and stretching the economic and social fabric of municipalities to their breaking point. But beyond providing a snapshot of the present conditions of the African housing market, the book offers recommendations and actionable measures for policy makers and other stakeholders on how best to provide affordable housing and alleviate Africa's housing deficit. This work will be of particular interest to practitioners, non-governmental organizations, private sector actors, students and researchers of economic policy, international development, and urban development.